Crop Phenomics: Current Status and Perspectives - Zhao, Chunjiang; Zhang, Ying; Du, Jianjun; Guo, Xinyu; Wen, Weiliang; Gu, Shenghao; Wang, Jinglu; Fan, Jiangchuan (Frontiers in Plant Science, 2019)
Reliable, automatic, multifunctional, and high-throughput phenotypic technologies are increasingly considered important tools for rapid advancement of genetic gain in breeding programs. With the rapid development in high-throughput phenotyping technologies, research in this area is entering a new era called 'phenomics'. The crop phenotyping community not only needs to build multi-domain, multi-level, and multi-scale crop phenotyping big database, but also to research technical systems for phenotypic traits identification and develop bioinformatics technologies for information extraction from the overwhelming amounts of omics data. Here, we provide an overview of crop phenomics research, focusing on two parts, from phenotypic data collection through various sensors to phenomics analysis. Finally, we discussed the challenges and prospective of crop phenomics in order to provide suggestions to develop new methods of mining genes associated with important agronomic traits, and propose new intelligent solutions for precision breeding.